Interpretasi Perintah Sujud pada Kisah Nabi Adam menurut Para Mufasir - Zulihafnani Zulihafnani; Novita Putri (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2021)
Prostration is proof of the closeness between beings to Allah Swt as their God, by placing his head on the ground as worship that is only done to Allah. This is different from the story of Prophet Adam, and God commanded the angels and demons to prostrate to Prophet Adam. This article attempts to discuss the meaning of prostration in the story of the Prophet Adam. The research method used is the method of maudhu'i which is the method of interpreting the verses of the Qur'an thematically. The type of research that the author uses is the type of literature research, by collecting data following the topic of discussion. The analysis technique that the author uses is descriptive analysis; that is, the author tries to understand the verses based on the interpretation of the scholars and also based on other sources. According to the commentators, this article discusses the command of prostration in the story of the Prophet Adam. The result of the research is the description of prostration in the story of the Prophet Adam in the Qur'an, which is included in various surahs such as surah al-Baqarah, al-Hijr, al-A’raf, al-Isra, al-Kahfi, Thaha, and surah Shad. There are also differences of opinion among scholars in interpreting the verses in which it explains the story of the command of prostration to the Prophet Adam. Sujud merupakan bukti ketaatan dan kedekatan makhluk dengan Allah Swt sebagai Tuhan. Sujud dilakukan dengan merendahkan diri, menundukkan badan dan meletakkan kepala di bawah sebagai bentuk penyembahan. Dalam pengertian tersebut, tidak ada sujud yang boleh dilakukan oleh makhluk selain kepada Allah. Namun di sisi lain, Allah Swt memerintahkan para malaikat dan iblis untuk sujud kepada Nabi Adam. Tulisan ini bertujuan untuk mengetahui makna sujud pada kisah Nabi Adam. Penelitian kepustakaan ini dilakukan dengan menggunakan metode maudhu’i untuk menemukan ayat-ayat yang terkait dengan tema yang dimaksud. Kemudian dianalisa secara deskriptif dengan memahami ayat-ayat melalui penafsiran para ulama dan sumber-sumber lain. Hasil penelitian menunjukkan bahwa deskripsi sujud pada kisah Nabi Adam dalam al-Qur’an terangkum dalam berbagai surah, yaitu QS. al-Baqarah, QS. al-Hijr, QS. al-A’raf, QS. al-Isra’, QS. al-Kahfi, QS. Thaha, dan QS. Shad. Dari ayat-ayat tersebut, diketahui bahwa Allah Swt memerintahkan para malaikat dan iblis untuk sujud kepada Nabi Adam sebagai bentuk penghormatan, bukan sebagai penyembahan.